Stratospheric Forecasting with NOGAPS-ALPHA - Allen, Douglas R.; Eckermann, Stephen D.; Coy, Lawrence; McCormack, John P.; Hogan, Timothy F.; Kim, Young-Joon (2004)
A new high-altitude version of the Navy Operational Global Atmospheric Prediction System (NOGAPS) is described and used to hindcast the unusual 2002 Antarctic stratospheric major warming. The new version, called NOGAPS-Advanced Level Physics with High Altitude (NOGAPS-ALPHA or NOGAPS-alpha) includes modifications to multiple components of the operational version, including the radiation scheme, gravity wave drag, vertical coordinate, and meteorological initialization. It also has a raised model top from 1.0 to 0.005 hPa and radiatively active prognostic ozone with parameterized photochemistry. A detailed comparison of the major warming period (September 2002) is done with operational NOGAPS (NOGAPS-op), operational ECMWF, and NOGAPS-alpha stratospheric forecasts. We examine the synoptic evolution of the middle stratospheric polar vortex as well as wave propagation diagnostics. The NOGAPS-op forecasts showed weaker wave activity compared to the analysis, which resulted in poorer predictions of the split stratospheric vortex. The situation improved in NOGAPS-alpha forecasts initialized with NOGAPS operational analyses, with stronger wave amplitudes and better forecasting of the split vortex. More significant improvements were found when NOGAPS-alpha was initialized with the ECMWF analyses, prompting plans for a NOGAPS reanalysis of this period. In Preprint Volume of the Symposium on the 50th Anniversary of Operational Numerical Weather Prediction, American Meteorological Society, University of Maryland, College Park, MD, June 2004. The original document contains color images.